2017
DOI: 10.1111/vox.12570
|View full text |Cite
|
Sign up to set email alerts
|

Novel intronic RHD variants identified in serologically D‐negative blood donors

Abstract: All identified RHD variants contain at least one mutation that probably affects splicing to generate D-negative phenotype. Hence, ethnic RhD antigen background must be considered when developing transfusion and obstetric strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…More than 300 variant alleles of RHD have been reported ( Kawano et al, 1998 ; Ye et al, 2007 ; Fichou et al, 2015 ; Chen et al, 2016 ; Ogasawara et al, 2016 ; El Wafi et al, 2017 ; Chun et al, 2018 ; Raud et al, 2019 ), including single-nucleotide polymorphisms (SNPs), small or large fragment deletions, gene rearrangements, and complete RHD deletions. The intron mutation disrupts a constitutive splice site, resulting in improper retention of an intron or activation of a cryptic splice site in the vicinity of the mutant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 300 variant alleles of RHD have been reported ( Kawano et al, 1998 ; Ye et al, 2007 ; Fichou et al, 2015 ; Chen et al, 2016 ; Ogasawara et al, 2016 ; El Wafi et al, 2017 ; Chun et al, 2018 ; Raud et al, 2019 ), including single-nucleotide polymorphisms (SNPs), small or large fragment deletions, gene rearrangements, and complete RHD deletions. The intron mutation disrupts a constitutive splice site, resulting in improper retention of an intron or activation of a cryptic splice site in the vicinity of the mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lacking fresh blood samples for RNA extraction, many functional studies mainly relied on recombinant plasmids. Hence, clinical transcriptome data and protein analysis are urgently needed to investigate genotype-phenotype mechanisms ( Liu et al, 2010 ; Fichou et al, 2015 ; El Wafi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed NGS effectiveness in resolving the molecular background of orphan antigens with an as yet unknown genetic basis. [49][50][51][52][53][54][55][56][57][58][59] The WES strategy based on genomic DNA from patients with detected antibodies and their relatives combined with appropriate variant filtering have revealed one SNV in the GYPA gene. 49 This discovery allowed the SARA antigen to join the MNS blood group system.…”
Section: Ngs In Revealing Unknown Blood Group Variationsmentioning
confidence: 99%
“…In a group of RhD negative individuals, El Wafi et al revealed five novel intronic RHD variants that probably affected the splicing of D protein. 59 Moller et al analyzed the genomic sequences of genes encoding 36 blood group systems from over 2500 individuals enrolled in the 1000 Genome Projects. 32 The study revealed 1241 non-synonymous variants.…”
Section: Ngs In Revealing Unknown Blood Group Variationsmentioning
confidence: 99%